PENGARUH METODE PEMBELAJARAN EKSPERIMEN TERHADAP NILAI RELIGIUS DAN RASA INGIN TAHU SISWA - Priatna, Oking Setia; Fitriah, Zahrotul (ATTA`DIB, 2015)
The aim of research is to know how the implementation of Experiment Method gives an effect to the students’ religious value and their curiosity. The research applied quantitative-descriptive method. This research found that method of experiment learning gives an effect both to the students’ religious value (from 44 to 73 in experiment class) and (from 40 to 48 in control class), and to the students’ curiosity (from 44 to 73 in experiment class) and (from 31 to 36 in control class). In conclusion, experiment method can increase both students’ religious value and their curiosity, so its method can be implemented in teaching learning process.